Fundamentals of soil stabilization - Firoozi, Ali Akbar; Guney Olgun, C.; Firoozi, Ali Asghar; Baghini, Mojtaba Shojaei (International journal of geo-engineering, 2017)
Clayey soils are usually stiff when they are dry and give up their stiffness as they become saturated. Soft clays are associated with low compressive strength and excessive settlement. This reduction in strength due to moisture leads to severe damages to buildings and foundations. The soil behavior can be a challenge to the designer build infrastructure plans to on clay deposits. The damage due to the expansive soils every year is expected to be $1 billion in the USA, £150 million in the UK, and many billions of pounds worldwide. The damages associated with expansive soils are not because of the lack of inadequate engineering solutions but to the failure to identify the existence and magnitude of expansion of these soils in the early stage of project planning. One of the methods for soil improvement is that the problematic soil is replaced by suitable soil. The high cost involved in this method has led researchers to identify alternative methods, and soil stabilization with different additives is one of those methods. Recently, modern scientific techniques of soil stabilization are on offer for this purpose. Stabilized soil is a composite material that is obtained from the combination and optimization of properties of constituent materials. Adding cementing agents such as lime, cement and industrial byproducts like fly ash and slag, with soil results in improved geotechnical properties. However, during the past few decades, a number of cases have been reported where sulfate-rich soils stabilized by cement or lime underwent a significant amount of heave leading to pavement failure. This research paper addressed the some fundamental and success soil improvement that used in civil engineering field.